A CASE REPORT OF PEDUNCULATED EXTRALUMINAL GASTROINTESTINAL STROMAL TUMOR (GIST) - Le , Ngoc Tu Tran; Le, Ngoc Quy; Nguyen , Anh Tuan; Dang, Nhu Thanh; Hoang , Minh Loi (Tạp chí Điện quang & Y học hạt nhân Việt Nam, 2021)
Gastrointestinal stromal tumors (GISTs) comprise a group of smooth muscle mensenchymal alimentary tract tumors of variable malignancy (1) GISTs may ouccur anywhere along the gastrointestinal tract, they are most commont located in the stomach (5060%) and the small intestine (30-35%), and less frequenty in the colon, rectum and esophagus (2). More rarely, GISTs may arise from other intra-abdoment soft tissues within the abdominal cavity, usually in the omentum, mesentery or the retroperitoneum called extra-Gastrointestinal stromal tumors (EGIST). Three macroscopic growth patterns of GIST: intraluminal, exophytic (extraluminal), and transmural tumors with the distribution was even (3). In this study, we describe case report of 70-year-old man was admitted to our hospital because of abdominal pain over 6 months with no pathological antecedent. Abdominal ultrasound (US) reveal a omental solid mass in left lumbar region, and on CT scan show a solid mass in left lumbar region in front of the descending colon, maesuring around 50x87x133mm with well-circumscribed, slight enhance with intravenous contrast, no hemmorrage or necrosis area, no calcification and not clearly separated from small-bowel. Patient has laparoscopic surgeon, diagnosis was a pedunculated exoluminal gastrointestinal stromal tumor (GIST). Histopathological examination report and the CD-117 immunoreactive score is suitable of endoscopically invisible medium sized.